2012
DOI: 10.1063/1.3699224
|View full text |Cite
|
Sign up to set email alerts
|

Electroluminescence from strained germanium membranes and implications for an efficient Si-compatible laser

Abstract: We demonstrate room-temperature electroluminescence (EL) from light-emitting diodes (LED) on highly strained germanium (Ge) membranes. An external stressor technique was employed to introduce a 0.76% bi-axial tensile strain in the active region of a vertical PN junction. Electrical measurements show an on-off ratio increase of one order of magnitude in membrane LEDs compared to bulk. The EL spectrum from the 0.76% strained Ge LED shows a 100nm redshift of the center wavelength because of the strain-induced dir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
62
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 21 publications
1
62
0
Order By: Relevance
“…Enhanced electroluminescence from Ge light-emitting diodes (LEDs) has been demonstrated based on tensile-strained Ge with different stressors, but power efficiency needs to be significantly improved for practical lasers [13][14][15][16]. Enhanced direct-bandgap photoluminescence has similarly been demonstrated [20][21][22].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Enhanced electroluminescence from Ge light-emitting diodes (LEDs) has been demonstrated based on tensile-strained Ge with different stressors, but power efficiency needs to be significantly improved for practical lasers [13][14][15][16]. Enhanced direct-bandgap photoluminescence has similarly been demonstrated [20][21][22].…”
Section: Introductionmentioning
confidence: 91%
“…Many approaches to inducing tensile strain for Ge lasers and more efficient light emitters have been demonstrated [11][12][13][14][15][16][17][18][19]. The first optically pumped Ge laser used 0.15% biaxial strain plus degenerate n-type doping to partly populate the Γ valley with electrons despite the indirect bandgap [2].…”
Section: Introductionmentioning
confidence: 99%
“…Initial research effort was put into creating thin-film Ge membranes suspended in air, and then transferring external strain via various methods, such as water pressure, gas pressure, and stressor layer [17,[22][23][24][25][26][27][28]. More recently, a few researchers have presented novel structures to induce large tensile strain in Ge, in which a small residual tensile strain in Ge can be greatly amplified due to geometric effects [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…However, under sufficient tensile strain Ge can becoming a direct band gap material and so a tensile-strained Ge crystalline membrane could be a useful platform for a Ge light source, or other Ge-based optical devices. Recently, thin (<1 lm) freestanding Ge membranes 22,23 and various other suspended structures 13 have been fabricated through relatively simple processing. Nam et al 22 and Kurdi et al is not homogenous in its properties then other effects apparently observed on further straining may be a composite from a spectrum of different strain values and in actuality luminescence may be shaper, rather than broader, in response to strain.…”
mentioning
confidence: 99%
“…Recently, thin (<1 lm) freestanding Ge membranes 22,23 and various other suspended structures 13 have been fabricated through relatively simple processing. Nam et al 22 and Kurdi et al is not homogenous in its properties then other effects apparently observed on further straining may be a composite from a spectrum of different strain values and in actuality luminescence may be shaper, rather than broader, in response to strain. 24 However, standard structural characterization such as transmission electron microscopy (TEM) and scanning probe microscopy of these membranes are difficult due to their fragility.…”
mentioning
confidence: 99%